A review of Parydra (Diptera: Ephydridae) from Brazil - Wayne N Mathis; Luciane Marinoni (Zoologia (Curitiba), 2011)
Species of the shore-fly Parydra Stenhammar, 1844 from Brazil are reviewed with an emphasis on the fauna from southern Brazil, where one new species, Parydra arcuata sp. nov. - state of Paraná, municipality of Castro (8 km N, 24º45.3'S, 49º58.9'W) -, has been discovered and is herein described. To facilitate identification of species, we have included a diagnosis of the genus. We have also provided illustrations of structures of the male terminalia for all included species.